PENGARUH MODEL DIFERENSIASI DENGAN PENDEKATAN DIFERENTIATED INSTRUCTION TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI SMA NEGERI 4 SUMATERA BARAT - Alvita, Natasya Alvita (JURNAL BUANA, 2026)
Low learning motivation among students and the learning atmosphere in the classroom is less conducive due to differences in learning needs. The aim of this research is to determine the effect of the differentiation model with a differentiated instruction approach on student learning outcomes in geography subjects at SMA Negeri 4 West Sumatra and to identify significant differences in geography learning outcomes between students taught with a differentiated instruction approach and students taught with the conventional model. The method used in this research is quantitative with quasiexperiment. Based on the results of data analysis, it can be concluded that the use of the differentiation model with a Differentiated instruction provides a significant positive influence on improving the learning outcomes of class XE1 students in the Geography subject at SMA Negeri 4 West Sumatra. The average value of student learning outcomes in the experimental class which uses the differentiation model with a differentiated instruction approach is significantly higher than the control class. This shows that the differentiation model with a differentiated instruction approach can be an effective alternative for increasing student learning motivation and facilitating students to learn according to their needs.Keywords : Diferensiasi,Differentiated Instruction,Learning Outcomes